Vasorelaxant and blood pressure lowering effects of alchemilla vulgaris: A comparative study of methanol and aqueous extracts - (:unkn) unknown (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2015)
Background: In the last decade, a growing interest particularly in determining the cardiovascular effects of herbal extracts took place among researchers. Objective: Herein, we aimed to investigate the microvascular and blood pressure lowering effects of two differently processed extracts of the same herb, Alchemilla vulgaris (Rosaceaea), which was revealed to contain high levels of vasoactive compounds. Materials and Methods: For the purpose, endothelium intact rat mesenteric arteries were mounted in a myograph system and contracted with prostaglandin F 2 (PGF 2: 3 x 10(5) M) or potassium chloride (K : 40 mM). Then, aqueous and methanol extracts were added at 0.01-10 mg/ml concentrations in a cumulative manner. Results: Both extracts produced relaxations in PGF 2 (3 x 10(5) M) precontracted arteries which were insensitive to the inhibitors of endothelium derived vasoactive substances namely, L (G) -nitro-L-arginine (10(4) M), ODQ (10(5) M) and indomethacin (10(5) M) or removal of endothelium. Opposite vascular effects were observed when extracts were applied in K precontracted arteries. In addition, oral administration of the methanol extract of Alchemilla vulgaris, but not the aqueous extract, reduced blood pressure significantly in L-NAME hypertensive rats. Conclusion: Our results demonstrated that the methanol extract of Alchemilla vulgaris has more prominent and favourable vascular effects in normal and experimental hypertensive conditions reinforcing its traditional use in cardiovascular disorders, in particular hypertension. These results most likely give rise to further studies to reveal its mechanism of action and clinical value of this herb.
Keywords: Alchemilla vulgaris; blood pressure; extract; mesenteric artery; vasodilatation; VASCULAR SMOOTH-MUSCLE; FLAVONOID QUERCETIN; GALLIC ACID; RAT; CONTRACTION